145 Objective assessment of cancer-related fatigue, cardiac muscle and autonomic nervous system function in a palliative population: a feasibility study. (14th March 2023) - Brady, Bernadette; Barrett, Michelle; King, Gerard; Wilkinson, Rory; Murphy, Ross; Walsh, Declan
Abstract : Introduction: Cancer-related fatigue is a common symptom whose pathophysiology may involve dysfunction of cardiac muscle & autonomic nervous system (ANS). Aim: Assess feasibility of objective measurement of fatigue, cardiac muscle & ANS function in a palliative population. Methods: Consecutive participants with cancer recruited from palliative outpatient clinic. Fatigue measured subjectively (brief fatigue inventory [BFI]) & objectively (grip strength, timed-up-and-go [TUG], sit-to-stand [STS]). A 2D transthoracic echocardiogram assessed cardiac function (systolic: ejection fraction [EF]; diastolic: isovolumic relaxation time [IVRT], LV filling velocities [E/A]. Myocardial strain analysed using EchoPAC software. Heart rate variability (HRV) recorded for five minutes each of spontaneous & paced breathing. SDNN: standard deviation of RR intervals; RMSSD: Root mean square of successive differences. Active stand identified postural hypotension. Participants completed an acceptability questionnaire. Results: 10 participants, 7 female. Mean age: 66 years (57–71). Cancer types: Lung, colorectal, breast, gastric, ovarian. Metastatic disease: n=10. BFI ≥3 (indicating fatigue): n=7 Median (Range): BFI 4.2 (0–8.9). Grip strength (kg force) 18 (9–39). TUG (s) 9 (7–23). STS (no. in 30s) 10 (0–15) Ejection fraction normal: 67.5%. Grade I diastolic dysfunction present (E/A 0.8, IVRT 96ms). HRV reduced: SDNN & RMSSD very low: 21.3, 11.5ms spont; 27.2, 19.2ms paced, normal >50, >42 respectively Strain significantly different (19.1, 24.3, p=0.02) in groups with/without fatigue. BFI correlated with HRV, TUG with Strain (0.875, p=0.001), & HRV. All found study acceptable: No participant withdrew. One participant each: unable to complete STS felt echo interfered with privacy found paced breathing 'bothersome' Conclusions: 1. Objective assessment of fatigue, cardiac muscle & ANS feasible, acceptable & warranted in palliative populations 2. Majority of participants fatigued subjectively & objectively 3. Significant diastolic dysfunction & loss of HRV present 4. Correlations between subjective & objective fatigue, myocardial strain & HRV 5. These bedside tests can be used in palliative populations to guide symptom management